The fusion of Toxoplasma gondii SAG1 vaccine candidate to Leishmania infantum heat shock protein 83-kDa improves expression levels in tobacco chloroplasts - Albarracín, Romina Mariel (2015)
Chloroplast transformation technology has emerged as an alternative platform offering many advantages over nuclear transformation. SAG1 is the main surface antigen of the intracellular parasite Toxoplasma gondii and a promising candidate to produce an anti-T. gondii vaccine. The aim of this study was to investigate the expression of SAG1 using chloroplast transformation technology in tobacco plants. In order to improve expression in transplastomic plants, we also expressed the 90-kDa heat shock protein of Leishmania infantum (LiHsp83) as a carrier for the SAG1 antigen. SAG1 protein accumulation in transplastomic plants was approximately 0.1–0.2 μg per gram of fresh weight (FW). Fusion of SAG1 to LiHsp83 significantly increased the level of SAG1 accumulation in tobacco chloroplasts (by up to 500-fold). We also evaluated the functionality of the chLiHsp83-SAG1. Three human seropositive samples reacted with SAG1 expressed in transplastomic chLiHsp83-SAG1 plants. Oral immunization with chLiHsp83-SAG1 elicited a significant reduction of the cyst burden that correlated with an increase of SAG1-specific antibodies. We propose the fusion of foreign proteins to LiHsp83 as a novel strategy to increase the expression level of the recombinant proteins using chloroplast transformation technology, thus addressing one of the current challenges for this approach in antigen protein production.